2019
DOI: 10.1111/agec.12486
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamic analysis of productivity growth of agri‐food companies

Abstract: This study analyzes the spatial dynamics in productivity growth and its components for a sample of agri‐food companies in Murcia (Spain) over the period 2005–2014. We find that productivity growth of a company is related to productivity growth of neighboring companies, in both the short and long term. The marginal effects of the different factors on productivity growth are stronger in the short run rather than in the long run. Land characteristics and economic territorial conditions have the largest marginal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
0
23
0
1
Order By: Relevance
“…(), Skevas and Grashuis (), Martínez‐Victoria et al . () and Skevas () used exact geographical coordinates (i.e. latitude and longitude) to test for the presence of spatial spillovers in firms’ inefficiency/productivity scores, with the results verifying their existence.…”
Section: Introductionmentioning
confidence: 99%
“…(), Skevas and Grashuis (), Martínez‐Victoria et al . () and Skevas () used exact geographical coordinates (i.e. latitude and longitude) to test for the presence of spatial spillovers in firms’ inefficiency/productivity scores, with the results verifying their existence.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a binary matrix is constructed in which, for every farm, the k smallest distances receive a value of 1 while all others a value of 0 (see e.g. Martínez‐Victoria et al ., 2019). While IVD results in larger weights on characteristics of DMUs in closer proximity, this weight matrix implicitly assumes that spatial influences extend far beyond the nearby vicinity.…”
Section: Methodsmentioning
confidence: 99%
“…Journal of Agricultural Economics published by John Wiley & Sons Ltd on behalf of Agricultural Economics Society dependence in efficiency or productivity in non-agricultural applications (Glass et al, 2016;Tsionas and Michaelides, 2016;Pede et al, 2018). For the agricultural sector, Areal et al (2012) identified spatial dependence in technical efficiency of dairy farms in the UK, Martıńez-Victoria et al (2019) found spatial spillovers in productivity growth for Spanish agri-food companies and Skevas and Grashuis (2019) identified spatial spillover effects on efficiency scores among farm cooperatives in the USA. I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They find a significant result showing that spatial spillover effects influence the technical efficiency of geographically close cooperatives. Martínez‐Victoria et al (2019) analyze the inherent spatial processes in the productivity growth of agri‐food firms located in the territory of Murcia (Spain). They corroborate previous studies finding a significant spatial interaction effect in the productivity growth of neighboring companies.…”
Section: Introductionmentioning
confidence: 99%